Prostatic fiducial markers implantation by transrectal ultrasound for adaptive image guided radiotherapy in localized cancer: 7-years experience - Vito Lacetera; Massimo Cardinali; Giovanna Mantello; Francesco Fenu; Giulia Sbrollini; Flavia Tombolini; Alessandro Conti; Stefania Maggi; Giovanni Muzzonigro; Andrea Benedetto Galosi (Archivio Italiano di Urologia e Andrologia, 2014)
Objective: we present our 7-years’ experience with fiducial gold markers inserted before Image-Guided Radiotherapy (IGRT) focusing on our echo-guided technique reporting early and late complications. Material and methods: 78 prostate cancer (PCA) patients who underwent fiducial markers placement for adaptive IGRT (period 2007-2014) were selected. Mean patient age was 75 years (range 60-81), mean PSA 7.8 ng/ml (range 3.1-10), clinical stage < T3, mean Gleason Score 6.4 (range 6-7). We recorded early and late complications. Maximum distance between the Clinical Target Volume (CTV) and Planning Target Volume (PTV) was assessed for each direction and the mean PTV reduction was estimated. Results: we describe in details our echo-guided technique of intraprostatic gold fiducial markers insertion prior to adaptative IGRT. We report rare early toxicity (5-7% grade 1-2), a mean PTV reduction of 37% and a very low late toxicity (only 3.4% bladder G3 and 8% rectal G2 side effects). Conclusion: Our technique of fiducial gold markers implantation for adaptative IGRT is safe and well-tolerated and it resulted helpful to reduce CTV-PTV margin in all cases; the effects on clinical practice seem significant in terms of late toxicity but further investigations are needed with longer follow-up.